Oral health education and assistance to improve oral hygiene among children with special needs at Sahabat Difabel Foundation, Aceh Besar - Yuli Fatzia Ossa; Ayudia Rifki; Muhammad Ansari Adista (Buletin Pengabdian Bulletin of Community Services, 2026)
Background and Aim: Every individual has a fundamental right to access health services, including children with special needs. This community service program aimed to improve oral health among children with special needs at the Sahabat Difabel Foundation, Aceh Besar. The activities included oral health education, clinical oral examinations, provision of modified toothbrush aids, and educational sessions on cerebral palsy management and prevention of decubitus ulcers. Methods: A total of 15 children aged 2–20 years with various conditions, including cerebral palsy, Down syndrome, multiple disabilities, hearing impairment, and intellectual disability, participated in this program. A modified toothbrush device, Alat Bantu Sikat Gigoe (ABASIGOE), was introduced to assist children with motor limitations in maintaining oral hygiene. In addition, parents were provided with a practical guidebook on maintaining general and oral health, along with education on preventing decubitus ulcers. Results: The results of the program demonstrated that integrated education and assistive tools can support improved oral hygiene practices and enhance caregivers’ knowledge. Conclusion: Children with special needs continue to face significant barriers to achieving optimal oral health, as reflected by the high prevalence of oral health problems and limited access to healthcare services.